PENGARUH MODEL CONTEXTUAL TEACHING AND LEARNIN BERBANTUAN MEDIA SANTARA TERHADAP KEMAMPUAN BERPIKIR KRITIS MATERI IDENTITAS MASYARAKAT SISWA KELAS IV SEKOLAH DASAR - Shinta Ainun Nafisah; Yulina Ismiyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was conducted to address the low level of elementary students’ critical thinking skills caused by teacher-centered instruction and limited use of contextual learning media. The research aimed to examine the effect of the Contextual Teaching and Learning (CTL) model assisted by SANTARA media on fourth-grade students’ critical thinking skills in learning community identity material. This study employed a quantitative approach using a Pre-Experimental One Group Pretest–Posttest Design. The sample consisted of 17 students selected through probability sampling. Data were collected using validated and reliable essay tests measuring critical thinking indicators and analyzed using normality tests and paired sample t-tests. The results indicated a significant improvement in students’ critical thinking skills after the implementation of the CTL model assisted by SANTARA media, as evidenced by a significance value of less than 0.05 and a substantial increase in mean scores from pretest to posttest. Improvements were also observed across all critical thinking indicators, with the highest gain in explanation skills. These findings suggest that contextual learning supported by interactive cultural media effectively enhances students’ higher-order thinking skills and promotes meaningful learning experiences in elementary education.